ASSESSMENT OF ALLERGIC RHINITIS SEVERITY SYMPTOMS USING VAS - simovic, sladjana stanimir (Medicinski časopis, 2017)
Objective: To examine the characteristics of patients with allergic rhinitis and assess the severity of symptoms by using a visual analogue scale. Metods: A observational prospective study was carried out among allergic rhinitis patients, who were referred by the primary care physician to the ENT Department of Health Centre Kragujevac. The assessment of severity of symptoms was performed using visual analogue scale (overall influence of all nasal or nasal and ocular symptoms, VAS score of 0 "nasal or nasal and ocular symptoms do not bother" to 10 "nasal or nasal and ocular symptoms are extremely bothered") during the first examination. Data was statistically analised with descriptive statistical methods, t-test, χ2 test test and logistic regression using by standard statistical software package (SPSS for Windows, version 19.0). Results: The majority of our participants were classified as having moderate to severe persistent allergic rhinitis. Severity of disease has a greater impact on the VAS score of disease duration. Average VAS score of all participants were 6,9±4,2. It was found that the severity of the disease and the presence of ocular symptoms in patients with allergic rhinitis have an impact on the VAS score (p<0,0001) and the use of therapy and sensitization to inhalant allergens not. Conclusion: Visual analog scale is a simple quantitative methods to assess the severity of allergic rhinitis. Keywords: allergic rhinitis, symptoms, visual analog scale.